Physical Fitness Level and Physical Education Learning Outcomes of Students of Elementary School 1 Rappocini, Makassar City - Saleh, Muhammad Syahrul (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine the level of physical fitness and physical education learning outcomes of students. The method used in this study is the regression method supported by a quantitative approach, following the problems studied, namely regarding ongoing events or incidents. The quantitative approach is a research approach that is carried out by measuring variable indicators so that a general description and at the same time conclusions can be obtained regarding the problem being studied. In this study, there are two variables involved, namely the independent variable is the level of physical fitness (X1) and the dependent variable is physical education learning outcomes (Y). The population in this study were all male students of Elementary School 1 Rappocini, Makassar City, grades III, VI and V with a population of 120 students, the sample used in this study were 40 male students of Elementary School 1 Rappocini, Makassar City with a sampling technique of random sampling or random system. The data collected in this study included physical fitness level tests and student learning outcomes. Based on the results of the research and discussion that have been presented, the following conclusion can be drawn: Physical fitness in students of Elementary School 1 Rappocini, Makassar City is in the Moderate category. Physical fitness has a significant contribution to the learning outcomes of physical education in students of Elementary School 1 Rappocini, Makassar City.